Combining Synchronous and Asynchronous Learning: Student Satisfaction with Online Learning using Learning Management Systems - Osman, Siti Zuraidah Md (Journal of Education and e-Learning Research, 2022)
Students’ satisfaction, knowledge, skills and attitude towards learning (KSAs), engagement and interaction in online learning are essential indicators in ensuring that the Learning Management System (LMS) is utilised effectively and efficiently. However, most students become passive listeners and observers during online teaching and learning activities on the LMS platform, both in synchronous and asynchronous learning. Therefore, this study aimed to identify student satisfaction in terms of KSAs, engagement and interaction with a combination of synchronous and asynchronous learning in online learning platforms. A questionnaire was distributed to 163 students from a higher education institution. The results showed that student satisfaction was at a high level in KSAs; there was a significant positive relationship between KSAs, interaction and student engagement which led to student satisfaction. Therefore, a teaching design which combines synchronous and asynchronous learning methods could be applied by educators to enhance students’ KSAs, interaction and engagement to help raise their satisfaction levels.